The Dark Side of Customer Relationship Management in the Luxury Segment of the Hotel Industry - Jaipuria, Akshay (2006)
Today, service organizations are shifting their focus from transactional exchange to relational exchange for developing mutually satisfying relationship with customers. Extended relationships are reported to have a significant impact on transaction cost and profitability, and customer lifetime value. Serving the customers, in true sense, is the need of the hour as the customer was, is and will remain the central focus of all organizational activities. The hotel industry, especially the luxury segment hotels needs to be purely customer-centric and focus on the customer needs and duly fulfill them.